Quality of Visual Cue Affects Visual Reweighting in Quiet Standing. - Renato Moraes; Paulo Barbosa de Freitas; Milena Razuk; José Angelo Barela (PLoS ONE)
Sensory reweighting is a characteristic of postural control functioning adopted to accommodate environmental changes. The use of mono or binocular cues induces visual reduction/increment of moving room influences on postural sway, suggesting a visual reweighting due to the quality of available sensory cues. Because in our previous study visual conditions were set before each trial, participants could adjust the weight of the different sensory systems in an anticipatory manner based upon the reduction in quality of the visual information. Nevertheless, in daily situations this adjustment is a dynamical process and occurs during ongoing movement. The purpose of this study was to examine the effect of visual transitions in the coupling between visual information and body sway in two different distances from the front wall of a moving room. Eleven young adults stood upright inside of a moving room in two distances (75 and 150 cm) wearing a liquid crystal lenses goggles, which allow individual lenses transition from opaque to transparent and vice-versa. Participants stood still during five minutes for each trial and the lenses status changed every one minute (no vision to binocular vision, no vision to monocular vision, binocular vision to monocular vision, and vice-versa). Results showed that farther distance and monocular vision reduced the effect of visual manipulation on postural sway. The effect of visual transition was condition dependent, with a stronger effect when transitions involved binocular vision than monocular vision. Based upon these results, we conclude that the increased distance from the front wall of the room reduced the effect of visual manipulation on postural sway and that sensory reweighting is stimulus quality dependent, with binocular vision producing a much stronger down/up-weighting than monocular vision.